2020
DOI: 10.1080/02827581.2020.1799066
|View full text |Cite
|
Sign up to set email alerts
|

Integrating data from National Forest Inventories into socio-cultural forest monitoring – a new approach

Abstract: Integrating data from National Forest Inventories into socio-cultural forest monitoring -a new approach

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Our study demonstrated the capacity of the new DSS prototype to provide enterprise-specific scenario estimates under changing climate and alternative management strategies, enabling stakeholders to take scientifically well-founded decisions for sustainable forest management. In particular, the new DSS offers: (1) a stronger link to inventory data and forest growth conditions in Switzerland by incorporating the new forest model SwissStandSim (Zell et al, 2020), the stand initialization approach by Mey et al (2021) and the allometric functions for tree biomass and carbon content based on the latest national forest inventory (Didion et al, 2019;Herold et al, 2019), (2) a climate sensitive framework, which is of increasing importance for strategic planning (Mina et al, 2017), (3) a widened portfolio of BES indicators, integrating also the socially important recreation function (e.g., Hegetschweiler et al, 2020), as well as an updated framework for harvested wood products and substitution effects for carbon sequestration (FOEN, 2020), and (4) a revised MCDA framework allowing stakeholders to perform trade-off analyses under different management strategies and weighting preferences. Altogether, the new DSS provides a flexible and dynamic tool for strategic (i.e., long-term) planning of sustainable forest management under changing climatic conditions and political/strategic goals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study demonstrated the capacity of the new DSS prototype to provide enterprise-specific scenario estimates under changing climate and alternative management strategies, enabling stakeholders to take scientifically well-founded decisions for sustainable forest management. In particular, the new DSS offers: (1) a stronger link to inventory data and forest growth conditions in Switzerland by incorporating the new forest model SwissStandSim (Zell et al, 2020), the stand initialization approach by Mey et al (2021) and the allometric functions for tree biomass and carbon content based on the latest national forest inventory (Didion et al, 2019;Herold et al, 2019), (2) a climate sensitive framework, which is of increasing importance for strategic planning (Mina et al, 2017), (3) a widened portfolio of BES indicators, integrating also the socially important recreation function (e.g., Hegetschweiler et al, 2020), as well as an updated framework for harvested wood products and substitution effects for carbon sequestration (FOEN, 2020), and (4) a revised MCDA framework allowing stakeholders to perform trade-off analyses under different management strategies and weighting preferences. Altogether, the new DSS provides a flexible and dynamic tool for strategic (i.e., long-term) planning of sustainable forest management under changing climatic conditions and political/strategic goals.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements comprise an automatic handling of input data (e.g., inventory datasets), a more efficient software framework for faster computation, and an extension of the indicator framework. Additional indicators could for instance address further aspects of timber production (e.g., sustainability indicators for forest operations, Schweier et al, 2019), forest infrastructure (Bont et al, 2019), biodiversity (e.g., species associated with different successional stages, Hilmers et al, 2018), recreation (e.g., Hegetschweiler et al, 2020) as well as soil-and water related indicators (e.g., groundwater recharge, Schwaiger et al, 2018). Further aspects of key importance for forest managers are information about the uncertainty of the DSS results (Knoke et al, 2016), as well as the monetarization of BES (Gret-Regamey et al, 2017).…”
Section: Climate Change Effects On Bes Provisioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Images with obvious human impact are mostly disliked in such studies. In previous studies examined the management effects on visitors' preferences in urban forests found that negative perceptions were held of forestry work signs including stumps and piles of cut trees (Heyman 2012;Tessa Hegetschweiler et al 2020). They further concluded that a key factor in the participants' preferences was "natural" versus "human-made".…”
Section: Discussionmentioning
confidence: 97%
“…However, expert surveys present several limits inherent to the methodology (e.g., time and cost, low response rate if the survey is not appropriately designed, potential biases in the analysis), which reduce their use and potential applications. To overcome the limitations of both of these methods, NFI data may be combined with stakeholder surveys that take technical considerations into account (Hegetschweiler et al 2020).…”
Section: Introductionmentioning
confidence: 99%